Older Persons in the jurisprudence of the Inter American Court of Human Rights - Ferrer Mac-Gregor, Eduardo (Política y Sociedad, 2023)
The purpose of this article is to note the advances in the jurisprudence of the Inter-American Court of Human Rights with respect to the elderly as a particularly vulnerable group prone to discrimination. It starts with the actions adopted in the universal and regional human rights spheres to recognize the specific rights of this group, highlighting the particular contributions of the Inter-American System for the protection of human rights. The jurisprudential analysis begins with the stage in which this group was tangentially referred to, to later analyze the current stage in which age is incorporated through interpretation as a category of special protection in Article 1.1 of the American Convention on Human Rights, noting the way in which it intersects with other categories protected by the Pact of San José itself. Particularly noteworthy is the differentiated approach recently adopted by the Inter-American Court, developing more rigorously the content and scope of the rights of the elderly, emphasizing the particular impact of human rights violations related to health, access to justice, economic security and the environment..
Keywords: Older persons; American Convention on Human Rights; Inter-American Court of Human Rights; Inter-American Convention on Protection the Human Rights of Older Persons; Social Rights; Right to Health; Access to Justice; Social Security; Right to Work; Right to the Environment